Mad dogs and (mostly) Englishmen: Colonial relations, commodities, and the fate of Inuit sled dogs - Tester, Frank (Études/Inuit/Studies, 2010)
The Qikiqtani Truth Commission was created by the Qikiqtani Inuit Association to examine events affecting Qikiqtanimiut between 1950 and 1980. Paramount among these was the fate of Inuit sled dogs. Dogs, unlike the snowmobiles that have replaced them, had no exchange value in a market economy. They enabled existential relations dependent upon traditional and personal skills rooted in Inuit culture and personality. It is understandable that their fate was identified by elders as an important focus of the Commission. The loss of dogs was both real and symbolic of cultural transformations that concern Inuit elders. As Inuit relocated to settlements, sled dogs became a liability for the Arctic administration. The Dog Ordinance of the Northwest Territories, intended to protect people from attacks, was at the same time a tool in the totalising agenda of a Canadian State committed to assimilating Inuit to Canadian norms, values, assumptions, rule of law, and settlement living. As Inuit moved to town in the 1950s and 1960s, the Dog Ordinance of the Northwest Territories was used to redefine dogs—previously seen as essential to Inuit lifestyles, to keeping Inuit out of town, away from welfare and living independently—as liabilities and commodities. Their replacement by snowmobiles introduced Inuit to new commodity relations. As a commodity essential to hunting, snowmobiles pose a serious challenge to Inuit reciprocity and ningiqtuq (sharing) relations and InuitQaujimajatuqangit (traditional knowledge).